REDUKSI RIPPLE TORSI MOTOR INDUKSI TIGA FASA DENGAN PENYEDERHANAAN PI-DTC - Yahya, Rahulfajri Ash-Shaffan; Djuriatno, Waru; Rusli, Moch. (Jurnal Mahasiswa TEUB, 2024)
In this study, the authors conducted simulations to simplify the algorithm contained in the SVM so that performance can be improved while maintaining its low complexity. Tests were conducted using simulations on MATLAB/Simulink software. Fromthe test results, it is known that the execution speed of the simplified SVM is 0.3 seconds faster than the conventional SVM. In addition, there is a slight decrease in torque ripple by 6% in the simplified SVM. From the results of all tests, the use of simplified PI-DTC is able to reduce torque ripple and reduce PI-DTC complexity. Keywords: PI-DTC, SVM, torque ripple, complexity, Simulink